Global Value Chains and Productivity : Micro Evidence from Estonia - Banh, Hang (IMF Working Papers; Working Paper, 2020)
The COVID-19 pandemic has led to an unprecedented collapse in global economic activity and trade. The crisis has also highlighted the role played by global value chains (GVC), with countries facing shortages of components vital to everything from health systems to everyday household goods. Despite the vulnerabilities associated with increased interconnectedness, GVCs have also contributed to increasing productivity and long-term growth. We explore empirically the impact of GVC participation on productivity in Estonia using firm-level data from 2000 to 2016. We find that higher GVC participation at the industry level significantly boosts productivity at both the industry and the firm level. Frontier firms, large firms, and exporting firms also benefit more from GVC participation than non-frontier firms, small firms, and non-exporting firms. We also find that GVC participation of downstream industries has a negative correlation with productivity. Frontier firms and large firms benefit more from GVC participation of upstream industries, while non-frontier firms and small firms benefit more from GVC participation of downstream industries. Our results suggest that policies designed to promote participation in GVCs are important to raise aggregate productivity and potential growth in Estonia.